TEACHERS' LEVEL OF KNOWLEDGE IN CANVA MEDIA LEARNING AT SDN NGRONGGO 2 KEDIRI - Rimawati; Tri Sulistyarini (EZRA SCIENCE BULLETIN, 2024)
This article intends to describe the effectiveness of using Canva as a learning medium and increasing teacher creativity. Globalization brings major changes in the order of people's lives. These changes are driven by the increasing development of science and technology, which has an impact on various sectors of life, including the field of education. The design of learning media today not only utilizes objects that can be found in everyday life but also utilizes the digital world. Canva is an application that can be developed in the process of creating Indonesian language learning media which really requires media as an introduction to information from abstract learning material content. Canva is an online design application, which provides a variety of graphic designs consisting of; presentations, posters, advertisements, flyers, graphics, banners, invitation cards, photo editing and Facebook covers. Canva learning media can be applied in various learning areas, including Indonesian language lessons in elementary school. In carrying out this research, descriptive research was used. This research uses a simple descriptive design with a collection tool in the form of a questionnaire. The research was conducted at SDN 2 Ngornggo KedIri with a sample size of 30 respondents. Samples were taken using Canva learning. The research results showed that more than half of the respondents (78%) had high knowledge about Canva learning and the rest (22%) had moderate knowledge about Canva learning. The recommendation for this research is to carry out further research by increasing the number of respondents